2018
DOI: 10.1177/1525822x17749386
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Thematic Saturation in Qualitative Data Analysis

Abstract: An important aspect of qualitative research is reaching saturation-loosely, a point at which observing more data will not lead to discovery of more information related to the research questions. However, there has been no validated means of objectively establishing saturation. This article proposes a novel quantitative approach to measuring thematic saturation based on a sound statistical model. The model is validated on two data sets from different qualitative research projects involving interviews, focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 14 publications
0
88
0
Order By: Relevance
“…Similarly, Lowe et al [ 25 ] estimated saturation and domain size in two examples and in simulated datasets, testing the effect of various parameters. Lowe et al found that responses were not independent across respondents and that saturation may never be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lowe et al [ 25 ] estimated saturation and domain size in two examples and in simulated datasets, testing the effect of various parameters. Lowe et al found that responses were not independent across respondents and that saturation may never be reached.…”
Section: Introductionmentioning
confidence: 99%
“…There has even been a recent call for the measuring of saturation through a so-called "saturation index" as a "validated means of objectively establishing saturation". 3 The problem is that fuzzy boundaries exist between words and numbers: qualitative and quantitative data are neither static nor binary. 2 So, although there is a multiplicity of ways in which qualitative research is quantified, and the use of numbers in qualitative research may cause us to gasp, what do we mean when we say … quantification in qualitative research?…”
Section: The Use Of Numbers Does Not Matter But What Matters Ismentioning
confidence: 99%
“…However, when working within an epistemic framework underpinned by subjectivity and multiple realities, quantification can actually serve to undermine more complex and nuanced interpretations of the meaning of qualitative data, thereby undermining the quality of our qualitative work. 3 For example, misrepresentation of qualitative data can occur when numbers (such as frequencies and percentages of themes) are employed in contexts in which participants have not been asked the same questions. 1,4 So, given the benefits but also the pitfalls of using numbers in qual- percentages should be employed only in the context of larger qualitative samples (ie n > 50), and (iv) that semi-quantification (the use of words like "majority", "minority", "few", "some" and "many") should be used only with justification.…”
Section: The Use Of Numbers Does Not Matter But What Matters Ismentioning
confidence: 99%
See 2 more Smart Citations